Stromal impact on tumor growth and lymphangiogenesis in human carcinoma xenografts - Hadler-Olsen, Elin (Springer-Verlag, 2010)
Squamous cell carcinomas (SCCs) arising in the oral cavity are associated with poor survival, mainly due to metastatic disease. In contrast, skin SCCs rarely metastasize and are usually curable. To study influence of tongue and skin stroma on cancer growth and induction of lymphangiogenesis, xenograft tumors of human carcinoma cells were established either in tongue or skin of BALB/c nude mice. Two oral and two skin SCC cell lines were used, as well as an endometrial adenocarcinoma cell line. Tongue tumors established from all cell lines were larger than corresponding skin tumors. Peritumoral lymphatic vessel density was up to five times higher in tongue than in corresponding skin tumors, and mRNA level of the lymphangiogenic growth factor vascular endothelial growth factor (VEGF)-C was twice as high in tongue tumors compared with corresponding skin tumors. Contrary to lymphatic vessel density, blood vessel density was higher in skin tumors than in tongue tumors. In a cohort of patient samples, lymphatic vessel density was found to be higher in tongue SCCs compared with skin SCCs, supporting a clinical relevance of our findings. Our results show that the tumor stroma has a profound impact on cancer growth and induction of lymphangiogenesis and angiogenesis. The difference in lymphatic vessel density between tongue and skin tumors may be important in directing metastatic potential of tumors arising in these organs.